2016
DOI: 10.1002/admi.201600371
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Enhancement of Biosolar Cells Employing Light Harvesting Complex II Incorporated with Core–Shell Metal@TiO2 Nanoparticles

Abstract: photosynthetic complexes in artifi cial phototovoltaic (PV) devices as "green" light harvesting antennas was proposed in hopes to use their extraordinarily efficient light absorption and energy transfer properties. Measurable photocurrent was initially achieved using a self-assembled membrane of RCs, [ 2,3 ] LHCI-RC core complexes, [ 4 ] or whole photosystems (PSI or PSII) [ 3,5 ] on conductive electrodes. The power conversion effi ciency (PCE) was increased notably after incorporating the photosynthetic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…This hierarchical architecture was demonstrated to suppress electron recombination with tri-iodide along with increase of electron lifetime and perform no hindering in mass transport using ionic liquid electrolyte. Recently, we employed a similar anatase TiO 2 nanotree array as photoanode scaffold for the LHCII sensitized biophotovoltaic cells [25]. This TiO 2 nanotree array can be simply grown on TiO 2 coated FTO glass by one-pot hydrothermal reaction without necessity of high-tech equipment [26].…”
Section: Fabrication Of Tio 2 Photoanodementioning
confidence: 99%
See 2 more Smart Citations
“…This hierarchical architecture was demonstrated to suppress electron recombination with tri-iodide along with increase of electron lifetime and perform no hindering in mass transport using ionic liquid electrolyte. Recently, we employed a similar anatase TiO 2 nanotree array as photoanode scaffold for the LHCII sensitized biophotovoltaic cells [25]. This TiO 2 nanotree array can be simply grown on TiO 2 coated FTO glass by one-pot hydrothermal reaction without necessity of high-tech equipment [26].…”
Section: Fabrication Of Tio 2 Photoanodementioning
confidence: 99%
“…It was recently reported that strong LHCII attachment can be obtained on a APTES grafted FTO substrate via electrostatic interaction between the anionic residues on the stromal side with cationic ─NH 3 + groups [14]. We adopted this approach and used APTES to functionalize the surface of TiO 2 thin film, TiO 2 nanotree array photoanodes and TiO 2 -encapsulated plasmonic NPs in LHCII sensitized solar cells [25]. Clear improvement in protein attachment is indicated by the more intense and uniform greenish color on the APTES modified photoanode (Figure 8a).…”
Section: Biosensitizations On Surface Modified Tio 2 Photoanodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon composite structures have been widely studied, such as core shell structure [38][39][40], which is considered as an effective structure to solve the above problems. For instance, Xia et al [41] synthesized MoO 3 /C nano-composites with a capacity of about 500 mA h g −1 at the 100 th cycle at a current density of 0.1 A g −1 for LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…11 We have also confirmed such effects in the DSSCs sensitized with natural light harvesting complex II. 12 In most DSSC operations, these three effects are mixed. It is necessary to design some model systems to elucidate the contributions of these distinctive effects in order to understand the complex mechanisms of the plasmon-enhanced DSSCs.…”
mentioning
confidence: 99%